The roles of FHL2 as a mechanotransducer for cellular functions in the mechanical environment - Fujimoto, Yukari; Nakazawa, Naotaka (Frontiers in Cell and Developmental Biology, 2024)
The cell has multiple mechanisms for sensing and responding to dynamic changes in the mechanical environment. In the process, intracellular signaling is activated to modulate gene expression. Recent studies have shown that multifunctional signaling molecules that link intracellular force and gene expression are important for understanding cellular functions in the mechanical environment. This review discusses recent studies on one of the mechanotransducers, Four-and-a-half LIM domains 2 (FHL2), which localizes to focal adhesions (FAs), actin cytoskeleton, and nucleus. FHL2 localizes to FAs and the actin cytoskeleton in the cell on stiff substrate. In this situation, intracellular tension of F-actin by Myosin II is critical for FHL2 localization to FAs and actin stress fibers. In the case, a conserved phenylalanine in each LIM domain is responsible for its localization to F-actin. On the other hand, lower tension of F-actin in the cell on a soft substrate causes FHL2 to be released into the cytoplasm, resulting in its localization in the nucleus. At the molecular level, phosphorylation of specific tyrosine in FHL2 by FAK, non-receptor tyrosine kinase, is critical to nuclear localization. Finally, by binding to transcription factors, FHL2 modulates gene expression for cell proliferation as a transcriptional co-factor. Thus, FHL2 is involved in mechano-sensing and -transduction in the cell in a mechanical environment.